The Utilization of “Jeda Nulis” Youtube Channel as Learning Media of Religious Tolerance for Virtual Communities - Mimi Sugiarti; Fauzi Fauzi (Al Qalam, 2021)
Abstract: This research is oriented to analyze the use of Youtube as a learning media of religious tolerance for virtual communities. The focus of the research is on the "jeda nulis" youtube channel with the content "toleran dalam berdakwah, dakwahkan toleransi." This research was conducted based on the reality of the rise of radical Islamic accounts that spread negative content in the form of teachings that are easy to disbelieve and convert to those who have different understandings and traditions. This research is descriptive-qualitative with a literature study approach. To explore the data obtained by watching and analyzing videos on related content. The results of the study found that Youtube can be used as a medium to spread the teachings of religious tolerance. In the youtube content mentioned above, Habib Husein collaborated with Christian and Buddhist religious figures, the three figures succeeded in bringing religious narratives that made virtual communities aware to better understand and apply the teachings of religious tolerance. religion is tolerance, but its people cannot necessarily be tolerant. The three religious leaders agreed that ego, lust, and group fanaticism must be eliminated in humans in order to be tolerant. If someone cannot become a brother in faith, then compete in goodness in the name of humanity. Because the real enemy for someone is itself so that must be clear first. Keywords: Religious Tolerance, Virtual Communities, Youtube.,